A construção institucional do direito “oficial”: fluxos e contrafluxos na tv justiça Potiguar - Honorato, Gustavo Henrique de Sá (2021)
Instructional, dogmatic law is seen as a given point of cultural reality, and the magistrates would be responsible for the mere application of the rules contained in the legal provisions, without having much room for the personalities and interventions of the particular elements of the judges. However, affiliated to the rhetoric chain, this work sees the Law, from the perspective of decision making, in which the people of the judges influence the way in which the judicial pronouncements. The central problem of this research is to verify how the decision-making process takes place, through the institutional channels stipulated by the model of national jurisdictional application. Starting from the premise that, in an environment of social massification, judicial decisions are also massified, taken in flux. However, precisely the authenticity and inventiveness of the agents inserted in the legal field can be decisive for breaking this pattern of functioning of the bodies responsible for making decisions, establishing the so-called counterflows. This research aims to understand this decision-making process, identifying the rhetorical strategies used by the agents in order to establish these counterflows. To this end, the ethnography of the legal discourse and the multimodal analysis of the TJ / RN sessions, televised by TV Justiça Potiguar, were applied. From the observation of the sessions, it was possible to verify which rhetorical strategies operate within the legal field, in order to imply the alteration of decision flows. The description of the scenes understood as flow and those that demonstrate the breaking of these patterns, counterflow, contributed to the achievement of the results that point out to be the proactive intervention of human agents, the demonstration of factual knowledge about the subjects and the management of social capital, the fundamental elements in the construction of Law, in an institutional environment. Thus, it can be inferred that, in fact, there is a process of decision-making massification, however, there is room for changes, markedly, from the rhetorical strategies pointed out